Calcium binding protects E-cadherin from cleavage by Helicobacter pylori HtrA. Issue 1 (December 2016) - Schmidt, Thomas; Goetz, Camilla; Huemer, Markus; Schneider, Gisbert; Wessler, Silja
Abstract Background The cell adhesion and tumor suppressor protein E-cadherin is an important factor in the establishment and maintenance of epithelial integrity. E-cadherin is a single transmembrane protein, which consists of an intracellular domain (IC), a transmembrane domain (TD), and five extracellular domains (EC). EC domains form homophilic interactions incis andtrans that require calcium binding to the linker region between the EC domains. In our previous studies, we identified the serine protease high temperature requirement A (HtrA) from the human pathogen and class-I carcinogenHelicobacter pylori (H. pylori ) as a bacterial E-cadherin-cleaving protease that targets the linker region of the EC domains, thereby disrupting gastric epithelial integrity. However, it remains unclear how calcium binding to the E-cadherin linker regions affects HtrA-mediated cleavage. Results Investigating the influence of calcium on the HtrA-mediated cleavage of recombinant E-cadherin (rCdh1) in vitro, we tested different concentrations of calcium ions and the calcium chelator ethylenediaminetetraacetic acid (EDTA). Calcium efficiently reduced HtrA-mediated E-cadherin fragmentation. Conversely, the addition of EDTA strongly increased cleavage, resulting in a ladder of defined E-cadherin fragments. However, calcium ions did not affect HtrA oligomerization and protease activity as monitored by degradation of the universal protease substrate casein. Finally, addition of ethyleneglycol-bis-tetraacetic acid (EGTA) slightly enhanced E-cadherin cleavage duringH. pylori infection of gastric epithelial cells. Conclusions Our results suggest that calcium blocks HtrA-mediated cleavage by interfering with the accessibility of calcium-binding regions between the individual EC domains, which have been identified as cleavage sites of HtrA.